Does Guanxi matter to nonfarm employment? - Zhang, Xiaobo; Li, Guo (Elsevier, 2003)
Because land is scarce, farmers in China increasingly have to rely on nonfarm activities to enhance their incomes. The functioning of rural nonfarm labor markets is therefore crucial in determining who has access to nonfarm employment. Previous studies have identified human capital as a key factor determining the selection of workers in the rural nonfarm economy. Using a detailed household survey of northern and northeastern China, this paper shows that guanxi (social networks), has also played an important role. With limited nonfarm job opportunities and poor market information, farmers with better social contacts are more likely to obtain nonfarm jobs. Moreover, guanxi has a larger effect on the nonfarm employment opportunities of male workers than female workers.